A note on count linearity in luminescence measurements using PMT modules$nshort communication - Kreutzer, Sebastian; Mittelstraß, Dirk (Ancient TL, 2025)
Deviations from anticipated instrumental readings in luminescence measurements can result in systematic uncertainties that are challenging to quantify. In this study, we address the issue of count rate linearity of photomultiplier modules commonly employed in luminescence readers. Considering instrumental thresholds and typical signal outputs, in most scenarios, this deviation is not a concern. However, in corner cases where detectors are operated in regions where non-linearity of count rates becomes significant, corrections are necessary. This is a well-known issue, but to the best of our knowledge, not all measurement systems utilise a correction. In this note, we provide some technical background and show that the impact on the equivalent dose can reach easily 2% even in conservative scenarios. We then demonstrate how this can be post-corrected using a straightforward dead-time non-linearity correction implemented in the R package ‘Luminescence’.